2013
DOI: 10.1177/1012690213475437
|View full text |Cite
|
Sign up to set email alerts
|

Discussing homosexuality on association football fan message boards: A changing cultural context

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(80 citation statements)
references
References 31 publications
4
75
0
1
Order By: Relevance
“…Using in‐depth interviews and observational data with young straight men, they demonstrated this use of language was not intended to marginalize or wound another person, and that it occurred in settings with little or no homophobia. While the history of these words means that these different interpretations may intersect (Butler ), cautioning against any simplistic understanding of gay discourse as necessarily having socially positive effects, the shift in young heterosexual men's use of language is nonetheless evidence of a broader change in how these words are used and understood (Cleland ; Lalor and Rendle‐Short ).…”
Section: From Homophobic To Homosexually Themed Languagementioning
confidence: 99%
“…Using in‐depth interviews and observational data with young straight men, they demonstrated this use of language was not intended to marginalize or wound another person, and that it occurred in settings with little or no homophobia. While the history of these words means that these different interpretations may intersect (Butler ), cautioning against any simplistic understanding of gay discourse as necessarily having socially positive effects, the shift in young heterosexual men's use of language is nonetheless evidence of a broader change in how these words are used and understood (Cleland ; Lalor and Rendle‐Short ).…”
Section: From Homophobic To Homosexually Themed Languagementioning
confidence: 99%
“…Wilcox, 2012). This leaves open an interesting avenue for further research into MMA fans' own online articulations of gender and sexuality, following recent studies of homophobia in fan postings within other, traditionally 'masculine' sports (Cleland, 2013;Kian, Clavio, Vincent & Shaw, 2011).…”
Section: Concluding Thoughtsmentioning
confidence: 99%
“…Cleland's (2011, 2012) research, for example, illustrates a significant decline of homophobia in British sports fandom. Their large-scale survey research revealed that 93% of 3500 soccer fans were acceptant of the presence of homosexuality in football -as well as on internet fan forums (Cleland, 2015;Cleland, Magrath, & Kian, 2016).…”
Section: Eric Andersonmentioning
confidence: 99%